PENYEBARAN HOAKS DALAM BISNIS DIGITAL: SEBUAH ANALISIS PADA KONTEN KREATOR MEDIA SOSIAL - Harjon, Losianus; Nuka, Ewaldus; Banis, Reginaldus; Yosef Adrianus Lado Hurint; Risaldo Fallo, Yohanes (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the dissemination of hoaxes in digital business by focusing on the role of social media content creators as key actors in online product promotion. The rapid growth of internet penetration in Indonesia has been accompanied by an increase in digital fraud and misleading content, partly driven by non-transparent promotional practices and exaggerated claims. Using a descriptive qualitative approach and secondary data from official government reports, online media, academic journals, and relevant regulations, this research applies the agenda-setting theory proposed by Maxwell E. McCombs and Donald L. Shaw as its analytical framework. The findings reveal that content creators hold a strategic position in shaping media agendas, influencing public agendas, and triggering policy agendas. The lack of promotional transparency, weak certification regulations, low digital literacy, and platform algorithm incentives contribute to the spread of misleading information. Therefore, strengthening transparency regulations, implementing certification mechanisms for creators in high-risk sectors, enhancing digital literacy, and optimizing platform supervision are essential to building a more ethical, safe, and accountable digital business ecosystem.